CARCINOMA OF THE MIDDLE EAR - Ghani, Rehman; Nabi, Ghulam; Akhtar, M.; Muluk, Saad (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: Cancer of the middle ear is an uncommon disease. It has been described in patients with long standing history of discharging ears. Two additional cases of carcinoma of middle car are described.